From Jihadism to Transnational Crime: The Evolution of the IMU Threat and ISIS Affiliates in Central Asia - Simbolon, Otniel Hizkia; Septianto, Ariel Mochammad; Pamungkas, Egi Aryo; Ginanjar, Fadlhan Firyal; Triwahyuni, Dewi; Putri, Sylvia Octa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The Islamic Movement of Uzbekistan or IMU is a militant group based in Central Asia. This group has been linked to regional jihadist movements for more than two decades. Over time the IMU changed its form because its ideology became weaker and military pressure continued to increase. The group also began to use the Islamic State or ISIS brand to strengthen its image. This paper explains how the IMU changed from an ideological jihadist group into a transnational criminal actor. This study uses a qualitative approach with descriptive analytical methods. The data comes from academic sources international agency reports and security policy documents. The findings show that ISIS influenced the IMU’s strategy. The IMU began to combine jihadist activity with organized crime. The group became involved in narcotics trafficking human smuggling and other illegal funding activities. This change shows how jihad became closely connected with criminal activity. This transformation has made the IMU a hybrid actor. The group now operates between terrorism and organized crime. This condition makes security responses in Central Asia more difficult. This paper argues that governments cannot rely only on traditional counterterrorism policies. They also need tools to reduce transnational crime in order to respond to the threat more effectively.